Dual band reflectarray for transmitter/receiver ground station drone tracking applications - Yobuamalan, Viwin Singh (Informacije MIDEM, 2025)
A dual-band, single-layer reflect array offering high gain has been developed for dual-polarized drone tracking applications. The reflect array unit comprises two center-notched spiral structures aligned orthogonally and is separated by an independent notchperfect rectangle element. Based on the reflect array unit design, a single layer 7 x 7 array, totally 49 elements for Horizontally Linearly Polarized (HLP) Ku-band transmission (12.4 – 14.8 GHz) and 49 elements for Vertically Linearly Polarized (VLP) X-band reception (10.7 – 12 GHz is designed with the phase changes of over 75o . This phase changes is obtained by adjusting the length of the notched spiral patch within the unit cell. Two distinct horn sources has been implemented to energize the orthogonal ports, supplying separate linear polarization for each frequency band. The efficiency is about 18.2 to 22% across different frequency bands, underscoring the array’s suitability for Drone Tracking applications. From the performance measures, it is found that the proposed dual-band reflect array is more suitable for drone ground station tracking applications. Additionally, this proposed structure minimizes design complexity and meets specifications of a low profile antenna with a simple structure and reduced weight.
Keywords: dual-band; dvopasovno; en odbojni sloj; low profile; nizek profil; odbojni niz; orthogonally linear polarization; ortogonalno linearna polarizacija; reflect array; single reflecting layer